Finite Element Analysis and Experimental Research of Gear Broken Teeth Fault of Engine - Jiang Zhinong; Jiang Bing; Zhang Yunxin; Che Yiquan; Zhang Feng; Zhang Jinjie (Jixie chuandong)
A finite element analysis of gear broken tooth fault of diesel engine based on the ANSYS Workbench is presented. The model of a pair of involute helical gear which is built by Pro / E parametric modeling is imported into ANSYS Workbench transient dynamics analysis module and the finite element analysis results under three conditions including normal gear,half- tooth broken gear and full- tooth broken gear are obtained.Then the results are compared with the experimental vibration data of gear broken tooth fault of diesel engine and comparison result shows that,during the operation of involute helical gear of diesel engine,the contact stress changes periodically and fluctuates obviously,clearly impact phenomenon exists and with the increasing of the degree of gear tooth damage,the impact force of the gear increase distinctly. The frequency of the maximum amplitude is the ignition frequency,the amplitude of rotating frequency corresponding to fault vibration is significantly greater than the normal rotating gear.